ANALISIS BIAYA RELEVAN UNTUK PENGAMBILAN KEPUTUSAN MENERIMA ATAU MENOLAK PESANAN KHUSUS PADA PT. BS POLYMER DI MAKASSAR - Ibrahim Ibrahim (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2015)
The aim of this study was to determine whether special orders can be accepted or not by using the relevant cost analysis. While the method of analysis separation semi-variable costs into fixed costs and variable costs, by using the method of least squares regression (least square regression method) and the relevant cost analysis of alternative elections with a special order and without special orders, where the variable used is the Contribution Margin. The results of the discussion and analysis is Based on the calculation of relevant costs, showed that PT.BS Polymer has not done a cost analysis relevant appropriately. From the analysis of the relevant costs, in particular the decision to accept or reject special orders showed that of the proposed alternative capable of providing benefits to the company. Based on the results of the analysis show that the special order special order of PT.Semen Tonasa and PT. Semen Batam acceptable